ZIS (Zakat, Infaq, and Sadaqah) and Economic Growth In Socio-Economic Dimension (Evidence : West Sumatera) - M Reza Tawakkal; Rida Rahim*; M. Fany Alfarisi (Riwayat: Educational Journal of History and Humanities, 2023)
This research aimed to investigate the influence of ZIS funds and economic growth on socio-economic issues in West Sumatra. For this study, panel data was collected using purposive sampling method. The study comprised 190 observations. Data was collected from 19 districts/cities in West Sumatra province from 2013 to 2022. The study used PLS as the regression method and subjected it to regression model selection test, classical assumption test, and GLS method approach. The findings indicated that both ZIS funds and economic growth had a significant role in reducing poverty, even zakat was more effective for alleviating poverty. In addition, both factors had a significant impact on improving the quality of life of the community. The study results can serve as input for the West Sumatra provincial government to enhance the collection of ZIS funds, which in turn can accelerate poverty alleviation and promote human quality development.